Perceived Organizational Support: analisis kritis dari sebuah model mediasi untuk variabel Organizational Commitment - Andi Syaputra; Rina Eka Widjayanti (Faculty of Economics and Business Udayana University, 2021)
There have been numerous works of literature investigating organizational commitment (OC) of an individual employee for the issue is considered necessary to receive more concern from time to time. This is also because an individual’s performance will become better along with the increase in OC. An individual’s intrinsic reward (IR) becomes one of the supporting factors to build individual employee commitment. In this study, we were investigating perceived organizational support (POS) as the other supporting aspect that builds better commitment. The objective of this study is to investigate the role of POS mediation in the correlation between IR and OC. The Structural Equation Modelling test indicates a positive response. POS succeeded in mediating IR against OC which means this study shows employee behavior in line with organizational goals